Assessment of knowledge about management of tooth avulsion among 7-14 years old school children in Nalgonda, Andhra pradesh - V Narayana Rao; S Suresh; V Viswanath; P Srinivas; T Devaki; Zaheer Ahmed (Wolters Kluwer Medknow Publications, 2013)
Background: The most serious dental injuries are avulsion of a tooth in children. Avulsion of permanent teeth accounts for approximately 0.5%-16% of dental trauma. The prognosis of replanted tooth mainly related to the injury of the periodontal membrane during the time the tooth is out of its socket. Dry storage of tooth will result in an irreversible injury to periodontal membrane with the result that the replanted tooth will be lost over a period of time. Objectives: To assess the present knowledge level of tooth avulsion among school children in Nalgonda. Materials & Method: A cross sectional questionnaire study was carried out on primary and secondary school children of Nalgonda, aged 7 -1 4 years. A total of 500 children were randomly selected from both government and private schools. A close-ended, pretested and self administered questionnaire which was written in local language was distributed. The questionnaire contained 10 questions pertaining to tooth avulsion. Results: Aboutl 8.8% of the children had experienced dental trauma in the past, Many children knew that a tooth could be knocked out but few (14.4%) had knowledge that same tooth could be replanted.48.3% said that washing tooth was necessary before reimplantation and majority (83.1%) said that they had not received any advice on tooth avulsion management. Conclusions: Overall assessment of the children showed a low level of knowledge regarding tooth avulsion and replantation principle. There is need for comprehensive dental educational programmes and oral health promotion amongst school children to improve their knowledge on tooth avulsion and replantation.